System informacyjno-decyzyjny rządowej administracji skarbowej - Gadomski, Sebastian (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article tries to identify information and decision systems of government revenue administration. The article characterizes the structure of revenue administration in Poland. It describes grades of management in revenue administration at macro and micro scale. The classification basic of decisions types has been made. The author emphasized that the implementation of appropriate information and communication technology is essential. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 50-59